THE STUDY OF THE INFLUENCE OF BOUNDARY CONDITIONS AND HETEROGENEITY IN THE PERFORMANCE OF THE NUMERICAL UPSCALING METHOD FOR ABSOLUTE PERMEABILITY - Steffens, Lindaura Maria; Santana Junior, Rogrio Tadeu; Isidoro, Carolina Mendes (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In a previous worka numerical upscaling technique for absolute permeability was developed. This method is a non-local technique that uses a cell layer around the upscaling zone to reduce boundary conditions influence. Upscaling zone is the set of cells of interest for upscaling, and the cell layers (or rings) are the adjascent cells in the fine grid. The following is an extension of the method and it studies the use of more than one ring around the upscaling zone and the effect of high heterogeneity areas in upscaling. Intuition says that a greater number of rings should improve the results, since it leads to reducing boundary conditions effect. However, the use of more layers implies in a higher complexity in the upscaling algorithm. In current study, the use of 1 and 2 rings to upscale a permeability grid was considered. Computational time and percentual error were compared for performance analysis. In addition, the method was compared to the harmonic and arithmetic average techniques. Flow simulations were performed usingfinite-differencemethod and incompressible single-phase flow based. The method was applied to SPE’s dataset 1 and some permeability fields generated by numerical probability distribution.